Differences in Viral Suppression and Renal Safety Effects between Tenofovir Alafenamide and Tenofovir Disoproxil Fumarate - Monmaturapoj, Teerapong (ศรีนครินทร์เวชสาร, 2016)
Tenofovir is a nucleotide reverse transcriptase inhibitors (NtRTIs) antiviral drug. Tenofovir disoproxil fumarate (TDF), the first approved oral prodrug of TFV, has been used and preferred in combination antiretroviral therapy for the treatment of human immunodeficiency virus (HIV) infection and recommended as first line treatment of chronic hepatitis B (CHB) viral infection. Although potent, low resistace rate and generally well tolerated, TDF can cause clinically significant renal toxicity. Due to TDF is unstable in plasma and poor penetration into the cell. Therefore, the high dose TDF is required in order to achieve adequate antiviral activity. Normally, intracellular tenofovir-diphosphate (TFV-DP) is responsible for the antiviral activity, higher circulating plasma levels of TFV from TDF have been associated with an increased risk of renal toxicity. A novel tenofovir prodrug tenofovir alafenamide (TAF) is more stable in plasma resulting in approximately ten times higher than intracellular concentrations of lymphoid cell of TFV-DP compared with TDF. Therefore, the lower dose of TAF than TDF is required for the treatment. Because of TAF’s reduced dose and the improved stability, plasma exposure of TFV is 90% lower with TAF than with TDF. Therefore, the lowering TFV equivalents administered reduces off-target kidney exposure. As mentioned previously, TAF is believed to reduce the risk of renal toxicity. From several clinical studies, TAF has been provided with non-inferior virological suppression to an already approved of TDF in the treatment of HIV-infected patients. However, TAF has significantly improved renal safety parameters with less proteinuria. Phase I clinical trail in CHB demonstrated that intracellular TFV-DP levels in primary human hepatocytes were 20-fold higher with TAF compared with TDF. The antiviral activity of TAF was comparable to TDF. However, the efficacy and safety of TAF in CHB patients is currently being studied in phase III clinical trial.